Customer Loyalty Modeling Based on Social Marketing in the Banking Industry - Pakravan, Fatemeh; Karimizand, Mahdi; Haghshenas Kashani, Farideh (Digital Transformation and Administration Innovation, 2025)
One of the most important concerns for banks in achieving maximum efficiency is customer loyalty. On the other hand, social marketing, as the newest marketing philosophy emphasizing individual and societal benefits alongside the interests of banks, represents a valuable approach for motivating customers and altering their attitudes toward the bank. The aim of this study is to develop a model for enhancing customer loyalty in the banking industry using social marketing. This study is qualitative in method and developmental in purpose. It is based on in-depth interviews with experts in the banking industry and branch managers of banks in Tehran. A purposive sampling method was employed. Data collection was carried out through library research and in-depth interviews with 14 experts. For data analysis, after reviewing the existing literature and prior research, the MAXQDA software and coding methodology were used to analyze the interview data. The findings of the study indicate that the dimensions of social marketing are related to customer loyalty. Through selective coding results, it was shown that trust, commitment, price, tools and customer expectations, causal conditions, employee behavior, staff training, facilities and technology, contextual conditions, bank characteristics, society and customer, intervening conditions, loyalty, satisfaction, and the sense of value represent core conditions, while cultural development, facilitative regulations, government support, and advertising constitute the strategic conditions that form the proposed model.